2003
DOI: 10.1177/1532673x02238578
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Primary Divisiveness On General Election Outcomes In State Legislative Elections

Abstract: Does a divisive primary contest harm a candidate's chances in the general election? This question is addressed in an analysis of legislative campaigns in nine states during the 1994 and 1996 election cycles. Findings indicate that primary divisiveness does affect general election outcomes but in the opposite direction than anticipated. Greater divisiveness in a candidate's primary leads to a higher vote share in the general election. Similarly, greater divisiveness in a general election opponent's primary lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
14
0
2
Order By: Relevance
“…Despite the conventional wisdom's wide acceptance, the search for supporting evidence often produced null or inconclusive findings. The most recent scholarship even indicates that the conventional wisdom may be wrong: challengers tend to do better when coming out of divisive primaries (Alvarez, Canon, and Sellers 1995;Arbour and McKenzie 2002;Herrnson 2000;Hogan 2003). Three distinct limitations in the study of divisive primary elections have produced this pattern of results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the conventional wisdom's wide acceptance, the search for supporting evidence often produced null or inconclusive findings. The most recent scholarship even indicates that the conventional wisdom may be wrong: challengers tend to do better when coming out of divisive primaries (Alvarez, Canon, and Sellers 1995;Arbour and McKenzie 2002;Herrnson 2000;Hogan 2003). Three distinct limitations in the study of divisive primary elections have produced this pattern of results.…”
Section: Discussionmentioning
confidence: 99%
“…The plausibility of these causal mechanisms notwithstanding, studies investigating whether or not divisive primaries actually harm the general election fortunes of party nominees have produced decidedly inconclusive results. Some studies have found that divisive primaries hurt candidates in the general election (Abramowitz 1988;Bernstein 1977;Segura and Nicholson 1995); others have found a mixed relationship (Born 1981;Hogan 2003;Kenney and Rice 1984) or none at all (Hacker 1965;Kenney 1988;Piereson and Smith 1975). Recent scholarship has even begun to turn the common wisdom on its head, finding that divisive primaries actually help U.S. House challengers (Alvarez, Canon, and Sellers 1995;Arbour and McKenzie 2002;Herrnson 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The conventional wisdom that hotly contested primaries can damage a party's chances in the general election is based on the theoretical work of Key (1953). Empirical literature that studied this conjecture produced mixed results: Abramowitz (1988), Bernstein (1977) and Lengle-Owen-Sonner (1995) find that intense primaries hurt candidates in the general elections, Alvarez-Canon-Sellers (1995) and Westlye (1991) find that intense primaries help candidates in the general election, Atkenson (1998) and Kenney (1988) find that general election prospects are not affected by the primary intensity, and, finally, Born (1981) and Hogan (2003) find mixed relationship. In this paper, we use theoretical analysis to shed light on the relationship between the intensity of the nomination process and general election outcomes.…”
Section: Mariana Agranovmentioning
confidence: 99%
“…Some studies have found that intense primaries hurt candidates in the general election (Abramowitz (1988), Bernstein (1977) and Lengle, Owen, and Sonner (1995)). Others have found a mixed relationship (Born (1981) and Hogan (2003)) or none at all (Atkenson (1998) and Kenney (1988)). And still others have found that intense primaries may actually help candidates in the general elections (Alvarez, Canon, and Sellers (1995) and Westlye (1991)).…”
Section: Divisive-primary Effectmentioning
confidence: 99%